Correlation of the Intra Ocular Pressure Measured by Non Contact Tonometer with the Perkins Applanation Tonometer and Study of Non Contact Tonometer as a Screening Tool - Vallabha K; Vijayamahantesh M. Bijapur (Al Ameen Medical College, 2017)
Background: Intra ocular pressure (IOP) measurement is essential in ophthalmological assessment as raised IOP is an important risk factor for development as well as progression of glaucoma. Aims: To correlate the IOP by the Non Contact Tonometer (NCT) with the Perkins Applanation Tonometer (PAT) and to study NCT as a screening tool. Materials and Methods: It is a comparative study on Patients attending Out Patient Department of Ophthalmology, from 1st December 2014 to 30th September 2016. We included 260 participants. Data collected using proforma, informed consent, history, ophthalmological examination. Patients were subjected to Non Contact Tonometry and Perkins Applanation Tonometry. 3 readings were taken for each method and mean calculated. Statistical analysis used: Paired-T test & Correlation-co-efficient. Sensitivity and Specificity were calculated for the NCT. Results: The NCT showed excellent agreement with the PAT. The correlation coefficient(r) of IOP measured by NCT and PAT is 0.879 and 0.894 for right eye and left eye respectively with p value <0.05, showed strong positive correlation between the IOP measured by NCT and PAT. The NCT also scored high as an effective screening tool. The NCT showed high sensitivity 95.5 and 94.3 for right eye and left eye respectively, high specificity 94.5 and 99.1 for right and left eye respectively, coming across an excellent agreement with PAT, using an IOP of more than/equal to 21 mm Hg with the PAT as the standard criterion. Conclusion: The current study shows that the NCT compares well with the PAT. The NCT can be used as a reliable screening tool.